2011
DOI: 10.2134/agronj2010.0161
|View full text |Cite
|
Sign up to set email alerts
|

Canopy Reflectance‐Based Nitrogen Management Strategies for Subsurface Drip Irrigated Cotton in the Texas High Plains

Abstract: Nitrogen fertilizer management in subsurface drip irrigation (SDI) systems for cotton (Gossypium hirsutum L.) can be very efficient when N is injected with the irrigation water (fertigated) on a daily basis. However, the daily rates and total amounts of N fertigation are uncertain. Normalized difference vegetative index (NDVI), calculated from weekly canopy reflectance measurements can guide N management in SDI cotton. The objective of this 3‐yr study (2007–2009) on an Acuff sandy clay loam (fine‐loamy, mixed,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(48 citation statements)
references
References 20 publications
3
44
0
Order By: Relevance
“…The site was planted on 20 May 2010 with Stoneville 5458 (ST 5458) and FiberMax 9180 (FM 9180) in 8, 1-m row plots that were 180 m long. There were 3 levels of N fertilizer in New Deal, a zero-N, intermediate N (50 kg ha −1 ) and full N rates (101 kg ha −1 ) determined as the first reflectance-based N strategy described in Bronson et al (2011). Each block consisted of 8 rows that were supplied by an individual irrigation and fertilizer injection station.…”
Section: Experimental Sites and Designsmentioning
confidence: 99%
“…The site was planted on 20 May 2010 with Stoneville 5458 (ST 5458) and FiberMax 9180 (FM 9180) in 8, 1-m row plots that were 180 m long. There were 3 levels of N fertilizer in New Deal, a zero-N, intermediate N (50 kg ha −1 ) and full N rates (101 kg ha −1 ) determined as the first reflectance-based N strategy described in Bronson et al (2011). Each block consisted of 8 rows that were supplied by an individual irrigation and fertilizer injection station.…”
Section: Experimental Sites and Designsmentioning
confidence: 99%
“…Gutierrez et al (2012) found that the correlation of cotton lint yield with NDVI was not significant at pinhead square, mid-bloom, or cut out (R 2 = 0.00-0.02) but was significant at early bloom and peak bloom (R = 0.46-0.69) in Arizona. Bronson et al (2011) reported that cotton lint yield was significantly correlated with amber and red DDVI at early bloom with R 2 = 0.06-0.30 and at mid-bloom with R 2 = 0.07-0.35 in Texas during 2007-2009. Bronson et al (2003) observed that the correlation of cotton lint yield with red NDVI was insignificant at early square, early bloom, or peak bloom at Ropesville, Texas in 2000, but was significant at early square, early bloom, and peak bloom with R 2 = 0.34-0.53 in 2000, and was insignificant at early square, but significant at early bloom and peak bloom with R 2 = 0.21 and 0.55, respectively, in 2001 at Lubbock, Texas.…”
Section: Discussionmentioning
confidence: 99%
“…Raper et al (2013) observed that the R 2 values of cotton leaf N concentration with NDVI from three different sensors (Crop Circle ACS-210, GreenSeeker Model 505, and Yara N Sensor) were between 0.08 and 0.69 in 2008, 0.06 and 0.72 in 2009, and 0.12 and 0.77 in 2010 during pre-square to peak bloom in Mississippi. Bronson et al (2011) reported that leaf N was significantly correlated with amber and red NDVI at early bloom with R 2 = 0.27-0.59 and mid-bloom with R 2 = 0.07-0.38 on irrigated corn in Texas during 2007-2009. Bronson et al (2003) found that the correlation of cotton leaf N concentration with red NDVI was insignificant at early square, early bloom, or peak bloom at Ropesville, Texas in 2000, but was significant at early square, early bloom, and peak bloom with R 2 = 0.18-0.19 in 2000, and was insignificant at early square, but significant at early bloom and peak bloom with R 2 = 0.…”
Section: Discussionmentioning
confidence: 99%
“…Zhao et al (2005) found that leaf chlorophyll was closely related to reflectance ratios using either R 708 /R 915 or R 551 /R 915 wavebands and there was a linear relationship between leaf nitrogen content and the reflectance ratio of R 517 /R 413 . In a subsequent study based on the observations from their original study, Bronson et al (2011) found that when NDVI values in the field decreased below a nitrogen-rich area and nitrogen was added to the treatment areas, there was a reduction in the amount of nitrogen applied by 33 % with no impact on lint or seed yield. They also found that the EONR varied from 23 to 75 kg·N·ha À1 among the 3 years of their study suggesting that the nitrogen response will differ among years due to growing conditions.…”
Section: Application To Other Cropsmentioning
confidence: 99%